Preparing to transition from pediatric to adult HIV-related care: qualitative assessment and model development. Issue 2 (2nd April 2016) - Kronschnabel, Kiersten; Puga, Ana; Eaton, Lisa
ABSTRACT: Prior to the emergence of highly active antiretroviral therapy (HAART) in the mid-1990s, HIV-infected adolescents and young adults (AYA) had poor long-term prognoses. The changing landscape of treatment has led to improved survival outcomes for HIV-infected youth, yet the health care structure for addressing the needs of this population is underdeveloped, in particular, when transitioning from pediatric to adult HIV care. Previous literature has proposed general recommendations for successful HIV transition programs, but limited model development exists to guide these recommendations. In order to better understand and address these shortcomings, the current study qualitatively assessed transition preparedness of 20 HIV-infected AYA (ages 13–24) at a comprehensive care center in the Southeastern United States. The study consisted of individual, semi-structured interviews exploring participants' preparation for transition. Through qualitative analysis of interview transcripts, a model was proposed to establish transition readiness. The model was based on three key themes encompassing multiple factors that influence transition readiness: (a) social cognition, (b) responsibility and skill development, and (c) health-related stressors. Based on the current study, we surmise that healthcare providers, patients, and their families can use this transition readiness model to better inform and prepare HIV-infected AYA to assume increased responsibility for their own health care.